Profiling DUBs and Ubl-specific proteases with activity-based probes - Geurink, Paul P. (Methods Enzymol, 2019)
Protein (poly-)ubiquitination is a posttranslational modification that plays a key role in almost all cellular processes. It involves the installment of either single ubiquitin (Ub) moieties or one of eight different polyUb linkage types, each giving a distinct cellular outcome. Deubiquitinating enzymes (DUBs) reverse Ub signaling by disassembly of one or multiple poly-Ub chain types and their malfunction is often associated with human disease. The Ub system displays significant crosstalk with structurally homologous ubiquitin-like proteins (Ubls), including SUMO, Nedd8, and ISG15. This can be seen with the existence of heterogeneous chains made from Ub–Ubl mixtures as well as the proteolytic cross reactivity displayed by several DUBs toward other Ubl systems. In addition, numerous pathogens have been found to encode Ub(l)-ligases and deconjugating enzymes in order to facilitate infection and fight the host immune response. Studying the activity of DUBs and Ubl-specific proteases, both human as well as pathogen-derived, gives fundamental insights into their physiological roles. Activity-based probes (ABPs) have proven to be valuable tools to achieve this, as they report on enzyme activities by making a (often irreversible) covalent complex, rather than on their relative abundance. In this chapter, we explain the potential of ABPs to assess substrate preferences, structural features, and activity of Ub and Ubl deconjugating enzymes. We further demonstrate the practical use of ABPs to (1) characterize the activity of viral proteases toward Ub and Ubls and (2) to gain more insight in the structural determinants of substrate preference of DUBs.